Children Bedroom Furniture of Preschool period according to child development - Nikoljski Panevski Elena (Ss. Cyril and Methodius University in Skopje, 2016)
In this thesis, the design considerations of a healthy and stimulating bedroom environment for preschool children are analyzed. In order to build up a multipurpose environment, the development of preschool children, the necessary items of furniture and the related design concepts are discussed. General design criteria are determined to constitute a guide for preschool children’s bedroom environment. In the light of these data, a research is conducted to analyze children’s development.
Keywords: Bedroom Environment for Preschool Children; Bedroom Furniture for Preschool Children; Child Development; Design Criteria; Plywood Material; Artisan Wooden Joinery